"Hindi Bayani/Not a Hero": The Linguistic Landscape of Protest in Manila - Monje, Jennifer (Social Inclusion, 2017)
This article examines the linguistic landscape of Manila during a protest march in November 2016 in response to the burial of deposed president Ferdinand Marcos at the Libingan ng mga Bayani (Heroes’ Cemetery). This article is situated among linguistic landscape of protest research (Kasanga, 2014; Seals, 2011; Shiri, 2015) where data is composed of mobile posters, placards, banners, and other ‘unfixed’ signs, including texts on bodies, t-shirts, umbrellas, and rocks. Following Sebba (2010), this article argues that both ‘fixed’ linguistic landscape and ‘mobile’ public texts are indices of the linguistic composition of cities, linguistic diversity, and ethnolinguistic vitality (Landry & Bourhis, 1997). Through a qualitative analysis of selected pictures produced during the protest march and uploaded onto social media, the multilingual nature of Manila is rendered salient and visible, albeit temporarily, and strategies of dissent are reflective of the language of the millennials who populated the protests.